Anatomical variations in human carotid bodies. Issue 11 (November 1988) - Khan, Q; Heath, D; Smith, P
Abstract : The variations in anatomical structure and position of both carotid bodies were noted in 100 consecutive subjects who came to necropsy. Considerable variations in form were found. Although most carotid bodies (83% on the right and 86% on the left) were of the classic ovoid type, an appreciable minority was bilobed (9% on the right and 7% on the left) or double (7% on the right and 6% on the left); 1% were leaf shaped. All these anatomical variants have to be distinguished from the pathologically enlarged carotid body that may have a smooth or finely nodular surface. Anatomical variants (such as the bilobed) may themselves enlarge as a consequence of carotid body hyperplasia.